Analysis of Changes in the Properties of Polymeric Components Joined by Resistance Welding - Kalwik, A.; Mordal, K.; Redutko, J. (Archives of Metallurgy and Materials, 2021)
The article has been devoted to issues connected with socket fusion welding, which is next to welding one of the methods of thermoplastic polymers joining. In this paper, the research was presented, which the aim was analysis of quality of joints obtained as a result of resistance welding of polypropylene pipes with diameter ø20 in the temperature range of 200÷230°C. To that end a Testo thermal imaging camera was used, flexural strength of the combined components was tested as well as the received weld was observed under a stereoscopic microscope. Conducted studies showed that the best results of joint are obtained during welding at 220°C and 230°C, while lower temperatures did not fully perform their function during the process of joining the pipe elements.
Keywords: polypropylene pipes; socket fusion welding; thermovision; bending strength; microscopic analysis